Hermeneutical Problem of Communicating Religiousexperience in Iqbal’s Thought - Hawasi, Hawasi (Jurnal Ilmiah Syi'ar, 2024)
This article elaborates the possibility of discursive language as a medium for explaining religious or mystical experience and how discursive language has position in such experience. Data of this research is based on Iqbal’s work on religious experience as found in his masterpiece, The Reconstruction of Religious Thought in Islam. Qualitative-descriptive method by hermeneutical perspective on language were used to elaborate and answer problems of religious and mystical experience according to Iqbal. The result of study shows that Iqbal tries to hermeneutically interprete religious experience or mystical experience in two different categories of realm. The first is language of religious or mystical experience which discusses the religious or mystical experience as something uncommunicable, untransformable, and unconceptualized. The second is language about religious or mystical experience which tries tospeaks about religious or mystical experience in the form of communicable and discursive language.